2021
DOI: 10.3389/frai.2021.543176
|View full text |Cite
|
Sign up to set email alerts
|

CNN-Based LCD Transcription of Blood Pressure From a Mobile Phone Camera

Abstract: Routine blood pressure (BP) measurement in pregnancy is commonly performed using automated oscillometric devices. Since no wireless oscillometric BP device has been validated in preeclamptic populations, a simple approach for capturing readings from such devices is needed, especially in low-resource settings where transmission of BP data from the field to central locations is an important mechanism for triage. To this end, a total of 8192 BP readings were captured from the Liquid Crystal Display (LCD) screen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Physiology or vitals: Through photographs of medical devices, vital signs such as blood pressure can be logged at the time of collection. Future work will focus on autotranscribing readings, as demonstrated in [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Physiology or vitals: Through photographs of medical devices, vital signs such as blood pressure can be logged at the time of collection. Future work will focus on autotranscribing readings, as demonstrated in [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, to increase the adoption of the PTEC HAT Programme in the subsequent implementation scaling phase, it is important to address this barrier and make the transmission of readings effortless and easy. One solution for the implementation scaling phase would be for the study team to explore alternative modes of transferring their readings, for example, via optical character reading (OCR) or manual submission [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In earlier work, we showed that deep-learning-based digit recognition from photos of medical device displays can help accurately capture such data [20]…”
Section: Background Mhealth System For Bp Monitoringmentioning
confidence: 99%
“…An additional "blank" character was incorporated for shorter sequences. In this work, the CNN-based model [20] was used to detect the sequences of digits. In this model a softmax classifier, receives extracted features from X by a convolutional neural network and returns the probability of each digit (Fig 5).…”
Section: Digit Recognitionmentioning
confidence: 99%
See 1 more Smart Citation